2011
DOI: 10.3748/wjg.v17.i30.3503
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of gadoxetic acid-enhanced MRI for hepatocellular carcinoma and dysplastic nodule

Abstract: Signal intensity in the hepatobiliary phase correlated with histological grade in the lesions that maintained portal blood flow, but did not correlate in lesions that showed decreased or defective portal blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…DCE-MRI is a powerful imaging modality to detect hepatocellular carcinoma (HCC) and for the subsequent planning of therapeutic strategies (14); maintaining spatial resolution is important for clinical use. This work has shown that our method is suitable for use in routine clinical data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCE-MRI is a powerful imaging modality to detect hepatocellular carcinoma (HCC) and for the subsequent planning of therapeutic strategies (14); maintaining spatial resolution is important for clinical use. This work has shown that our method is suitable for use in routine clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…However, it requires high temporal resolution and therefore sacrifices in terms of spatial resolution and/ or coverage. It is also incompatible with the routine clinical Gd-EOB-DTPA protocol, which acquires baseline breath-hold data with high spatial resolution in the arterial and portal phases and in the hepatobiliary phases (14).…”
mentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…HCC that is hyperintense on HBP has a higher grade of tumour differentiation and vice versa. [76][77][78][79][80] HCC with iso-/ hyper-enhancement on HBP has a lower risk for vascular invasion and recurrence, [81][82][83] and lower levels of expression of poor-prognostic immunohistochemical / progenitor cell markers including alpha-fetoprotein, protein induced by vitamin K absence or antagonist II, epithelial cell adhesion molecule, cytokeratin 10, and glypican-3. 18,82,84 Signal intensity, morphology, and signal heterogeneity in HBP are poor prognosticators.…”
Section: Gd-eob-mri As a Biomarkermentioning
confidence: 99%